2021
DOI: 10.1186/s13018-020-02156-w
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanics study on ligamentous injury in anterior-posterior compression type II pelvic injury

Abstract: Background Anterior-posterior compression (APC) type II pelvis fracture is caused by the destruction of pelvic ligaments. This study aims to explore ligaments injury in APC type II pelvic injury. Method Fourteen human cadaveric pelvis samples with sacrospinous ligament (SPL), sacrotuberous ligament (SBL), anterior sacroiliac ligament (ASL), and partial bone retaining unilaterally were acquired for this study. They were randomly divided into hemipel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Notably, the symptoms that have the significant impact on the quality of life for lumbosacral plexus injury patients are related to urinary and bowel function. Sacral neuromodulation is a treatment method that involves applying electrical pulses to the sacral nerves to stimulate effector organs like the bladder, urethral sphincter, and anal sphincter, thereby restoring their normal function 10 12 . Numerous clinical studies have demonstrated the significant clinical efficacy of this treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the symptoms that have the significant impact on the quality of life for lumbosacral plexus injury patients are related to urinary and bowel function. Sacral neuromodulation is a treatment method that involves applying electrical pulses to the sacral nerves to stimulate effector organs like the bladder, urethral sphincter, and anal sphincter, thereby restoring their normal function 10 12 . Numerous clinical studies have demonstrated the significant clinical efficacy of this treatment method.…”
Section: Discussionmentioning
confidence: 99%